Evaluación de la eficacia de Plata Coloidal sobre el complejo de enfermedades en el cultivo de arroz (Oryza sativa. L)” - Figueroa Planas, Marco Paul (2020)
The present work was carried out in the Experimental Farm "El Palmar" of the Technical University of Babahoyo, located at Km 12 of the Babahoyo - Montalvo road. The objective of the experimental work was to evaluate the efficacy of Colloidal Silver on the disease complex in rice cultivation (Oryza sativa. L). The treatments studied were 0.20 Lha-1, 0.25 Lha-1 and 0.30 Lha-1. The experimental design used was completely randomized blocks with 4 treatments and 3 repetitions. The test was carried out during the months of January to May and the edaphoclimatic conditions during the development of the research were conducive to the infestation of Rhizoctonia solani, Sarocladium oryzae and Gaeumannomyces graminis. However, the doses of colloidal silver that were evaluated did not minimize the incidence of these pathogens.